Synthetic and Natural Fibrous Scaffolds for Soft Tissue Engineering Applications - Khoo, Weily; Koh, Ching Theng; Lim, Shing Chee (Universiti Teknologi Mara (UiTM) Malaysia, 2017)
Fibrous scaffolds have been extensively studied as grafts for damaged tissue, owing to their physical architecture mimicking the native tissues like articular cartilage and skin. Developing mechanical robust fibrous scaffolds is therefore a critical issue to prevent scaffold failure that limits their applications in tissue engineering. This paper demonstrates our latest development of synthetic and natural fibrous scaffolds having physical architectures and mechanical properties comparable to that of native biological soft tissues. Synthetic fibrous scaffold was produced from gelatin solution using electrospinning technique while natural fibrous scaffold was extracted from small intestinal submucosa (SIS) of cattle. The SIS membrane was first decellurized and further reinforced with alginate hydrogel to form 3D composite scaffold. The physical architectures of both synthetic and natural fibrous scaffolds including thickness and microstructure morphology were characterized. SIS fibrous membrane reinforced with alginate hydrogel demonstrated more than 10 times of increment in scaffold thickness. Through scanning electron microscope (SEM) visualization, the synthetic fibrous scaffold demonstrated microstructures that mimic nanometer fiber and porous structure of soft collagenous tissues. Uniaxial tensile and fracture tests were performed to determine the tensile properties and fracture toughness of fibrous scaffolds. Both types of scaffolds showed tensile strength (0.81 – 38.30 MPa) and fracture toughness (0.86 – 32.52 kJ/m2) comparable to natural soft collagenous tissues. The developed tissue engineered scaffolds not only exhibit physical architectures mimicking native tissue structures but also demonstrate mechanical properties comparable to the native soft tissues.